Associations between the use of β-adrenoceptor acting drugs and the risk of dementia in older population - Cui, Shishuang; Fang, Fang; Cui, Peijing; Jiang, Qianwen; Xu, Shaoqing; Xu, Zhihong; Hu, Jia'An; Li, Feika (Frontiers in Neurology, 2022)
Objective: age-related decline within the noradrenergic system is associated with reduced cognition. β-adrenoceptors are widely expressed in brain as well as in peripheral. Medications targeting β-adrenoceptor activity have been widely used in older adults. The aim of this study was to explore the associations of β- adrenoceptor acting drugs and the risk of dementia in older population. Methods: subjects and their information were collected from the electronic medical records (EMR) database. Propensity score matching strategy was conducted to select control participants for users of β2-agonists or β-antagonists, respectively. Logistic regression analysis was performed to estimate the risk of dementia with use of β2-agonists or βantagonists. Results: a total of 1429 participants in the EMR database were included in the study. Use of β2-agonists was strongly associated with a decreased risk of dementia (OR = 0.324, 95% confidence interval [CI]: 0.149-0.707, P = 0.005). This decreased risk showed a statistically signiﬁcant inverse time-dependent pattern (Ptrend = 0.014). However, use of nonselective β-antagonists significantly correlated with an increased dementia risk (OR = 1.961, 95% CI: 1.144-3.359, P = 0.014), although no time-dependent manner was found (Ptrend = 0.220). There was no association between selective β1-antagonists usage and dementia risk (OR = 1.114, P = 0.625). Conclusions: use of β- adrenoceptor acting drugs seems to be associated with the risk of dementia. Pharmacological interventions modulating β2- adrenoceptor activity might be a potential target in therapeutics for dementia.